Pendekatan Berpikir Kritis Siswa Kelas VI pada Pembelajaran IPA di MIS Al-Anwar - Embun Sakara Ungu; Fanny Syahfitri; Lyna Luthfiyyah Azzahra; Mahfuzha Pane; Aufa Aufa (Journal on Education, 2023)
MIS Al-Anwar Medan has implemented the 2013 curriculum trial and students' critical thinking habits when learning science are the emphasis of the 2013 curriculum. Getting used to thinking in a scientific approach is not easy, challenging, and requires preparation. This study aims to analyze students' critical thinking habits in science learning according to the 2013 curriculum which applies a scientific approach at MIS Al-Anwar Medan. The survey method was carried out at MIS Al-Anwar Medan in the odd semester of the 2022/2023 school year. The natural science topic being studied is Electrical Quantities. Data on the application of the scientific approach in science learning is collected by observation. The population of this study were all students of class VI MIS Al-Anwar Medan. Sampling was carried out by convenience sampling and class VI students of MIS Al-Anwar Medan as the research sample. Research data were analyzed descriptively.